ULASAN KANDUNGAN METABOLIT SEKUNDER DAN KAJIAN BIOAKTIVITAS PADA RUMPUT TEKI (Cyperus rotundus L.) - Nurbah, Sahriana Putri; Sitorus, Saibun; Hairani, Rita (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Nutgrass (Cyperus rotundus L.) is one of the Cyperaceae family plants which is this plant belongs to weed. However, it is often used by the Chinese people as a traditional medicine. This review aimed to determine the bioactivity of nutgrass based on their secondary metabolite content. This review was carried out by Literature Review Article method from various journals through Google Scholar and Science Direct. The results of this review indicated that nutgrass has important bioactivities such as antioxidants, antidiabetic, anti-inflammatory, anticancer and antibacterial. Based on the review of those articles, it can be concluded that nutgrass has several important potency for human health to be further studied. Keywords: Cyperus rotundus L, Bioactivity, Secondary Metabolites